Note: Proof of principle of a new type of cluster beam source with potential for scale-up - Richard Palmer (Review of Scientific Instruments, 2016)
We introduce a new type of cluster beam source based on the assembly of (metal) clusters within a condensed (rare gas) matrix. The “Matrix Assembly Cluster Source” employs an ion beam to enhance collisions between metal atoms in the matrix and to sputter out clusters to form a beam. We demonstrate the formation and deposition of gold and silver nanoclusters with mean size tunable from a few atoms to a few thousand atoms. The cluster flux is equivalent to a current nanoAmp regime but potentially scalable to milliAmps, which would open up a number of interesting experiments and applications.